2013
DOI: 10.5935/1808-8694.20130058
|View full text |Cite
|
Sign up to set email alerts
|

Audiometric evaluation after stapedotomy with Fisch titanium prosthesis

Abstract: The Fisch-type titanium stapes piston prosthesis presented outcomes consistent with the literature and can be used safely in stapedotomy procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
1
6
0
6
Order By: Relevance
“…The air-bone gap with titanium in the study of Boleas-Aguirre et al [21] with an average closure of 16.31 dB which was found to be significant. Ataide et al [22] found out that the mean low-frequency postoperative air-bone gap was In our study of 30 ears operated, 12 ears had excellent improvement at 3 months post operatively, 4 ears had good improvement, 1 ear fair improvement and 2 failure cases by the end of 3 months post op. In the study conducted by Ahmed et al [24], postoperatively good hearing improvement was seen in 56.7%, fair improvement in 30% and poor results in 10% cases.…”
Section: Surgical Factorssupporting
confidence: 44%
“…The air-bone gap with titanium in the study of Boleas-Aguirre et al [21] with an average closure of 16.31 dB which was found to be significant. Ataide et al [22] found out that the mean low-frequency postoperative air-bone gap was In our study of 30 ears operated, 12 ears had excellent improvement at 3 months post operatively, 4 ears had good improvement, 1 ear fair improvement and 2 failure cases by the end of 3 months post op. In the study conducted by Ahmed et al [24], postoperatively good hearing improvement was seen in 56.7%, fair improvement in 30% and poor results in 10% cases.…”
Section: Surgical Factorssupporting
confidence: 44%
“…In 2013, Oeken 23 published a study of 256 cases of stapedotomy in which the postoperative air–bone gap was ≤10 dB in 220 cases (86%). In 2013, Ataide et al 24 observed the same result in 75.8% of patients undergoing stapedotomy. Therefore, the audiometric results obtained in the present study are consistent with those in the literature.…”
Section: Discussionmentioning
confidence: 76%
“…In 2013, Ataide et al observed the same result in 75.8% of patients undergoing stapedotomy. 11 In 2006, Vincent et al performed a prospective study in which the results of 3050 stapedotomies were analyzed over a period of 14 years. 12 The mean preoperative and postoperative airbone gap was 25.6 and 1.7 dB, respectively, and the gap was 10 dB in 94.2% of cases.…”
Section: Discussionmentioning
confidence: 99%